Influence of the Seed Loophole and Bottleneck on Quantity and Quality of Organic Maize Seed in the U.S. Midwest - Endres, A. Bryan; Andrade Laborde, Juan E.; Bohn, Martin O.; Formiga, Alice K.; Goldstein, Walter A.; Marriott, Emily E.; Ugarte, Carmen M.; Wander, Michelle M. (Frontiers in Agronomy, 2022)
A maize-based case study conducted in the U.S. Midwest determined whether consolidation of seed-production and sales pipelines or the influx of non-treated non-GMO seed are reducing the diversity and availability of organic maize (corn) seed. It also evaluated the prospects for participatory networks to improve organic seed quality. Methods included a literature review, farmer-focus groups, network activities, a workshop with seed producers, and a survey of merchants of organic maize seed. Though organic standards promote the use of certified organic seed, implementing regulations created an ‘organic seed loophole’ that permits organic farmers to use non-treated, non-GMO seed produced in conventionally managed fields. This research examined the scope of the loophole and its impacts on seed quality which was defined in different ways by network participants. Perceptions of seed adequacy were influenced by the markets farmers, grain buyers, and breeders serve. Producers growing for commodity markets that prized yield most highly were unconcerned about the continuing use of the loophole or seed derived from breeding programs managed with conventional practices. Producers and buyers engaging in de-commodified markets are more interested in organic breeding programs that prioritize phenotypic- and use-related traits imparting environmental or novelty value. An audit of seed sales suggests that the volume of organic seed available may be adequate as approximately 75% of organic maize produced in the U.S. is from certified organic seed. Just about a quarter is sourced through the regulatory loophole even though production costs of conventionally produced seed are 40-100% less than the cost to produce hybrids grown on certified organic ground by crossing non-GMO parent lines. This cost differential and competition from grain imports exert significant pressure on seed price, making it difficult to garner investment and innovation needed to improve seed diversity by developing inbred lines able to withstand weed, pest, and disease pressure. Strategies to increase organic seed quality and maize functional diversity include selection for compositional and phenotypic traits (e.g., nutritional value, rhizosphere function, and ecosystem service provision) and use of innovative public-private partnerships, sharing networks and intellectual property protections to overcome economic bottlenecks constraining organic seed quality.